Effect of medium supplementations and extraction conditions on cellulase production through solid state fermentation of oil palm empty fruit bunches - Vita Wonoputri; Jansen Wijaya; Joevin Saudalimka; Ronny Purwadi (Indonesian Journal of Biotechnology, 2024)
In this study, cellulase enzyme was produced through solid state fermentation (SSF), employing oil palm empty fruit bunches (EFB) as the primary substrate. Two key aspects were explored to enhance crude enzyme yield, which are medium supplementation effects during SSF and cellulase recovery. During medium supplementation, glucose and/or Tween 80 were added alongside EFB substrate and other nutrients. Enzyme yield was determined using a filter paper assay and expressed as enzyme activity. The initial addition of glucose during fermentation led to increased crude enzyme activity, as measured by the filter paper assay. The peak crude enzyme activity was observed with the addition of 3 mg of glucose, with higher amounts showing no further increase in activity. Conversely, the addition of Tween 80 did not yield any significant increase in crude enzyme activity across all concentrations tested. The extraction conditions were varied to study cellulase recovery, specifically by adjusting the solid‐to‐solvent ratio and the number of extraction stages. Higher enzyme activity was achieved with lower solid‐to‐liquid ratios, as the increased solvent volume facilitated greater enzyme extraction. However, increasing the number of extraction steps did not significantly affect the resulting cellulase activity. Overall, this research underscores the need for further process optimization for cellulase production via SSF, utilizing the widely available EFB in Indonesia.